Recurrent Solitary Fibrous Tumor (Intracranial Hemangiopericytoma) Treated With a Novel Combined-Modality Radiosurgery Technique: A Case Report and Review of the Literature - Allen, Alexander J.; Labella, Dominic Angelo; Richardson, K. Martin; Sheehan, Jason P.; Kersh, Charles R. (Frontiers in Oncology, 2022)
Solitary Fibrous Tumor (SFT) is a rare and aggressive mesenchymal malignancy with a predilection for recurrence after treatment. We report a case of a central nervous system SFT initially treated with subtotal surgical resection. Forty-four days post-resection, the tumor had demonstrated radiographic evidence of recurrent disease within the post-operative bed. Gamma Knife (GK) radiosurgery treatment was delivered in a “four-matrix” fashion targeting the entire surgical cavity as well as three nodular areas within this wide field. This treatment was delivered in one fraction with a stereotactic head frame for immobilization. A consolidation radiosurgery treatment course was then delivered over three additional fractions to the resection bed using a linear accelerator and mesh mask for immobilization. The total biologically effective dose (BED) was calculated as 32.50 Gy to the surgical bed and approximately 76.50 Gy to each nodular area. Almost three years post-operatively, the patient is alive and without radiographic or clinical evidence of disease recurrence. To our knowledge, no prior experiences have documented treatment of SFT using a mixed-modality, multi-fraction radiosurgery technique like the method detailed in this report. Our experience describes a novel adjuvant radiosurgery approach to treating SFT that maximizes radiation dose to the target with a single head frame placement. We believe this novel radiosurgery method should be considered in cases of low-grade SFT post-resection.